Traumatic avulsion of the eyeball: a case report - Das, Anamika D.; Juneja, Stuti V.; Ganvit, Shankar S. (International Journal of Research in Medical Sciences, 2020)
Ocular trauma is very common, but globe avulsion along with optic nerve avulsion is a rare clinical event. Blunt trauma during a road traffic accident can cause rupture or avulsion of the globe and the outcome can range from complete recovery on repositioning to visual loss because of globe perforation or optic nerve injury. Here, authors report a case of a 20-year-old male who presented with history of a road traffic accident causing severe facial injuries. The physical examination revealed oedema and ecchymoses over the right side of the face with avulsion of the right eyeball anteriorly outside the orbit along with avulsion of the optic nerve. The visual acuity in the injured eye was no perception of light and the direct pupillary response was absent. Computed tomography revealed fracture of the roof and lateral wall of the right orbit. As the eye was not salvageable, enucleation surgery was done. Insertion of an ocular prosthesis for rehabilitation was planned. The presentation, investigations, surgery and follow-ups are described.